2002
DOI: 10.1046/j.1442-2042.2002.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up of clinical stage I testicular cancer patients: Cost and risk benefit considerations

Abstract: Background: Regardless of the way it is managed, a high cure rate has been achieved for recurrent low-stage testicular cancer. Achieving a balance between survival and the patient's inconvenience and expense during follow-up, has therefore become an important issue. Methods: Prognoses and recurrence patterns were investigated in 39 patients with stage I nonseminomatous germ cell tumor of the testis (NSGCT), and 82 patients with stage I seminomatous germ cell tumor of the testis (SGCT), who underwent high orchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(64 reference statements)
0
7
1
Order By: Relevance
“…This change in relapse pattern has also been discussed by Taylor et al (2001) suggesting that pelvic imaging should particularly be considered when relapse from seminoma was suspected. In contrast to other series of PA or dog-leg radiotherapy for stage I seminoma (Logue et al 2003;Kakehi et al 2002), we also observed Weld edge recurrences without involvement of pelvic nodes in ten patients. Furthermore, approximately 20% of all relapses included retroperitoneal lymph nodes.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This change in relapse pattern has also been discussed by Taylor et al (2001) suggesting that pelvic imaging should particularly be considered when relapse from seminoma was suspected. In contrast to other series of PA or dog-leg radiotherapy for stage I seminoma (Logue et al 2003;Kakehi et al 2002), we also observed Weld edge recurrences without involvement of pelvic nodes in ten patients. Furthermore, approximately 20% of all relapses included retroperitoneal lymph nodes.…”
Section: Discussioncontrasting
confidence: 79%
“…Even though the optimal schedule of follow-up remains to be deWned, posttreatment surveillance is routinely recommended with the aim to detect relapse from seminoma as well as contralateral second cancers (Krege et al 2008b;Albers et al 2005;Souchon et al 2002). A number of publications have depicted on the topic of follow-up in testis cancer in general (Souchon et al 2002;Spermon et al 2004) or with a more speciWc focus like cost-eVectiveness (Buchholz et al 1998;Sharda et al 1996;Kakehi et al 2002), the role of tumor markers (Trigo et al 2000), or the use of chest imaging (Harvey et al 2002). To our knowledge, there have only been three previous publications on the speciWc requirements for posttreatment surveillance after paraaortic radiotherapy in stage I seminoma based on two large patient cohorts (Claßen et al 2005;Livsey et al 2001;Taylor et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our own results, Sokoloff et al [20] found a 10% increase in total costs between 1994 and 2000, mainly driven by higher expenditures for outpatient visits and ambulatory surgery. This might reflect the close follow-up of patients on AS when this concept was new at the end of the nineties [18]. …”
Section: Discussionmentioning
confidence: 99%
“…In 2001, Kakehi et al [18] calculated costs for an AS regime for the first year after orchiectomy for a cohort of 121 patients with CS I TC treated at their institution in Japan between 1970 and 1997. Expenditures were estimated at about EUR 1.910, which is noticeably above our own calculation, which showed costs of about EUR 430 for the same period.…”
Section: Discussionmentioning
confidence: 99%
“…There is concern that non-compliance may translate into a decrease in disease specific survival. (Colls et al, 1999;Gels et al, 1995;Kakehi, Kamoto, Kawakita, & Ogawa, 2002;Raghavan et al, 1988) Nevertheless, the true impact of non-compliance on survival is unknown. A national surveillance study in New Zealand failed to correlate non-compliance with compromise in cure.…”
Section: Follow Up For Surveillancementioning
confidence: 99%